EFFECT OF SOME CATIONS ON THE GLUCOSE OXYDASE BIOSYNTHESIS OF Aspergillus niger 9.4 - Hường, Nguyễn Thuý; Hiến, Ngô Tiến; Thu, Nguyễn Minh; Thuỷ, Khuất Thị; Châu, Trần Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY The glucose oxydase enzyme (GOx) (EC 1.1.3.4) binds to beta-D-glucopyranose (a hemiacetal form of the six-cacbon sugar glucose) and aids in breaking the sugar down into its metabolites. GOx is a dimeric protein that catalyzes the oxidation of beta-D-glucose into D-glucono – 1,5- lactone (which then hydrolyzes to gluconic acid) using molecular oxygen and releasing hydrogen peroxide. GOx can be used in the removal of either glucose or oxygen from foodstuffs in order to improve their storage capability. GOx can be biosynthesed by fungi Aspergillus niger and Penicillium. The effect of various cations, such as Fe2+, Cu2+, Zn2+, Mn2+ and Co2+ on the simultaneous production of glucose oxidase and catalase by Aspergillus niger 9.4 were investigated. Among the five cations, Zn2+ caused negative effect on GOx biosynthesis, two ions Fe2+ and Co2+ had positive influences on GOx biosynthetic process. The mutual influences between Fe2+ and Co2+ on GOx synthesis were also studied according to applied mathematic plan of Box –Wilson. In the medium, which was added FeSO4 (0.027 g/l) and CoCl2 (0.042 g/l) GOD enzyme activity (612.42 U/gr of biomass) was much higher than the sample with individual ion Fe2+ or Co2+ (maximum of GOD enzyme activity reached 290.77U/gr and 278.4 U/g).